2021
DOI: 10.1186/s12887-021-02686-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pediatric sepsis in the pediatric intensive care unit of king Abdulaziz Medical City, Jeddah, Saudi Arabia

Abstract: Background Pediatric sepsis remains a significant cause of morbidity and mortality worldwide. This study aimed to identify the incidence of sepsis and septic shock among patients admitted to the pediatric intensive care unit (PICU) of a tertiary center in Saudi Arabia.  Patients' demographics and risk factors associated with sepsis-related mortality were also investigated. Methods A retrospective cohort study was conducted in the PICU of King Abdul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…23 The highest independent mortality risk factors in our patients as determined by logistic multivariate regression analyses were higher pSOFA, MV requirement, and high levels of PSP and copeptin and low levels of APOA5. Our results are consistent with a previous study 27 in which the univariate logistic regression analysis of variables revealed that increased mortality in PICU patients with sepsis was significantly associated with an increase in pSOFA score (>4) and MV use. Multivariate regression analysis of an increase in pSOFA score (>4) was significantly associated with increased mortality, with a calculated odds ratio of 3.6 (95% CI, 1.30-9.93).…”
Section: Discussionsupporting
confidence: 93%
“…23 The highest independent mortality risk factors in our patients as determined by logistic multivariate regression analyses were higher pSOFA, MV requirement, and high levels of PSP and copeptin and low levels of APOA5. Our results are consistent with a previous study 27 in which the univariate logistic regression analysis of variables revealed that increased mortality in PICU patients with sepsis was significantly associated with an increase in pSOFA score (>4) and MV use. Multivariate regression analysis of an increase in pSOFA score (>4) was significantly associated with increased mortality, with a calculated odds ratio of 3.6 (95% CI, 1.30-9.93).…”
Section: Discussionsupporting
confidence: 93%
“…Matics et al found that the best threshold of pSOFA for differentiating mortality rate was >8 ( 9 ). In another single center study, a pSOFA Score >4 was associated with a significant increase in mortality ( 18 ).…”
Section: Discussionmentioning
confidence: 98%
“…5 9 Established screening tools such as the Paediatric Early Warning Score may support the timeliness of detecting clinical deterioration in children that can lead to sepsis. 10 Recently, adaptations to the Sequential Organ Assessment Score (SOFA) for paediatric patients and neonates have shown promise in identifying children at risk for mortality with sepsis 11 ; however, it is controversial whether these scores provide value in low-resource environments. [12][13][14] Development and implementation of algorithms such as the Sepsis Prediction and Optimisation Therapy that can analyse electronic health data in real time to provide a rule-based approach to initiate a physical sepsis screen have also been reported.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%